Effectiveness of warm water compresses in lowering body temperature in children with febris - Fredy Akbar K; Farmin Arfan; Suprapto Suprapto; Mariska Triyani Toratte (Journal Interdisciplinary Health, 2025)
Introduction: Febrile illness is a common clinical condition in children, often caused by viral or bacterial infections, and if not properly managed, can lead to serious complications such as seizures, dehydration, and altered consciousness. While pharmacological treatments like antipyretics are commonly used, non-pharmacological approaches like warm water compresses can be safe and effective alternatives. This study aimed to evaluate the effectiveness of warm water compresses in reducing body temperature in febrile children. Methods: This descriptive case study involved two pediatric patients aged 1 and 3 years diagnosed with febris. Each child received warm water compress treatment twice daily for three consecutive days. The compress was applied to specific areas (forehead, armpits, and groin) for 15–20 minutes using a towel soaked in 37–40°C water. Body temperature was measured with a digital thermometer before and after each intervention session. Observations also included behavioral responses and parent interviews to assess comfort and satisfaction. Results: The intervention demonstrated a significant decrease in body temperature among both patients. On average, there was a temperature reduction of 0.4°C to 1.0°C after each session, with a consistent downward trend over three days. Both children exhibited improved comfort and less irritability, and parents expressed satisfaction with the method as a supportive home care technique. Conclusion: Warm water compresses are effective as a non-pharmacological intervention in lowering febrile temperature in children. The method is safe, simple, and well-accepted, making it a viable option in clinical and home settings. Healthcare providers and parents are encouraged to utilize warm compresses to respond to febrile episodes, reducing over-reliance on medications and promoting safe, supportive care practices for children